Pengaruh Komitmen Guru-guru Swasta dalam Mengatasi Turnover Intention - Masri, Agustinus Nong; Susar, Aljuprianus (UMSU, 2025)
Maintaining strong and stable teacher performance is a serious task for current educational resource governance. Every year, school principals work hard to bring in new, competent staff to fill subjects that occur due to vacancies caused by teachers leaving school or their jobs. This research aims to prove the relationship between private teacher commitment and turnover intention. A quantitative correlational approach is the method used in carrying out research. The sample for this research was private teachers in East Nusa Tenggara Province with a sample of 200 respondents. Data analysis used a simple linear regression method and used SPSS version 26. The results of data processing showed that there was a negative and significant influence of teacher commitment on the intention to resign from work. By increasing teacher commitment, it can reduce the tendency for turnover intention to occur. Planned and sustainable strategies need to be promoted to reduce teacher turnover intention and increase their commitment to remaining in their jobs.